2017
DOI: 10.1002/wat2.1255
|View full text |Cite
|
Sign up to set email alerts
|

More than just snowmelt: integrated watershed science for changing climate and permafrost at the Cape Bounty Arctic Watershed Observatory

Abstract: The Cape Bounty Arctic Watershed Observatory (CBAWO) was established in 2003 to investigate the hydrological processes and impacts associated with climate and permafrost change in the High Arctic. Comprehensive data collection at the paired watersheds has spanned a period containing both the coldest and warmest melt season conditions, including the recent decade that is the warmest on record. Through this period, the hydrological regime has transitioned from a nival (snowmelt) dominated to increased importance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 50 publications
(159 reference statements)
0
50
0
Order By: Relevance
“…Thus, the summer of 2016 did not seem to be influenced by the event anymore. This short-lived sediment mobilization differs from major disturbances such as active-layer detachments or retrogressive thaw slumps, which impact sediment delivery in streams over many seasons (Bowden et al 2008;Frey and McClelland 2009;Lamoureux and Lafrenière 2009;Kokelj et al 2013;Lamoureux and Lafrenière 2017). Along with the increased sediment flux in 2015, we observe higher chloride concentrations and a slightly reduced alkalinity compared with the other years.…”
Section: Hydrological Responsementioning
confidence: 56%
See 1 more Smart Citation
“…Thus, the summer of 2016 did not seem to be influenced by the event anymore. This short-lived sediment mobilization differs from major disturbances such as active-layer detachments or retrogressive thaw slumps, which impact sediment delivery in streams over many seasons (Bowden et al 2008;Frey and McClelland 2009;Lamoureux and Lafrenière 2009;Kokelj et al 2013;Lamoureux and Lafrenière 2017). Along with the increased sediment flux in 2015, we observe higher chloride concentrations and a slightly reduced alkalinity compared with the other years.…”
Section: Hydrological Responsementioning
confidence: 56%
“…Hysteresis patterns for calcium and potassium are clockwise across catchments with varying permafrost coverage (Petrone et al 2007). The majority of SS is transported during the snowmelt season (Braun et al 2000;Forbes and Lamoureux 2005;Cockburn and Lamoureux 2008;Lamb and Toniolo 2016;Lamoureux and Lafrenière 2017), although high amounts of sediment may also be mobilized during summer rainfall events (Lewis et al 2005;Dugan et al 2012;Lamb and Toniolo 2016). Clockwise suspended sediment discharge hysteresis behaviour suggests a limitation and therefore rapid exhaustion of sediment that can be mobilized during rainfall (Dugan et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Kokelj et al () examined solute concentrations in the subarctic Peel River (Canada) and found that summer Na:SO 4 significantly decreased in the past 40 years as a result of RTSs increase. We do not have long‐term data for this site, but based on the scientific literature (Lafrenière & Lamoureux, ; Lamoureux & Lafrenière, ), we assume that past disturbances have influenced hydrochemical composition.…”
Section: Discussionmentioning
confidence: 99%
“…Further, our data only provide insights into catchment processes during the summer. Snowmelt is the largest hydrological event of the year (M. Woo, 2012) and responsible for major matter export from Arctic rivers (Fouché et al, 2017;Lamoureux & Lafrenière, 2018;Laudon et al, 2004;Petrone et al, 2006). Incorporating all seasons into the water balance and hydrochemical export studies is essential to assess lateral fluxes into the ocean.…”
Section: 1029/2019jg005505mentioning
confidence: 99%
See 1 more Smart Citation